Effects of cycling versus running training on sprint and endurance capacity in inline speed skating - Stangier, C.; Abel, T.; Mierau, J.; Hollmann, W.; Strüder, H. K. (Journal of Sports Science & Medicine, 2016)
The purpose of this study was to compare the effects of running versus cycling training on sprint and endurance capacity in inline speed skating. Sixteen elite athletes (8 male, 8 female, 24 ± 8 yrs) were randomly assigned into 2 training groups performing either 2 session per week of treadmill running or ergometer cycling in addition to 3 skating specific sessions (technique, plyometrics, parkour) for 8 weeks. Training intensity was determined within non-specific (cycling or running) and effects on specific endurance capacity within a specific incremental exercise test. Before and after the intervention all athletes performed a specific (300m) and one non-specific (30s cycling or 200m running) all-out sprint test according to the group affiliation. To determine the accumulation of blood lactate (BLa) and glucose (BGL) 20 µl arterialized blood was drawn at rest, as well as in 1 min intervals for 10 min after the sprint test. The sport-specific peak oxygen uptake (VO2 peak) was significantly increased (+17%; p = 0.01) in both groups and highly correlated with the sprint performance (r = -0.71). BLa values decreased significantly (-18%, p = 0.02) after the specific sprint test from pre to post-testing without any group effect. However, BGL values only showed a significant decrease (-2%, p = 0.04) in the running group. The close relationship between aerobic capacity and sprint performance in inline speed skating highlights the positive effects of endurance training. Although both training programs were equally effective in improving endurance and sprint capacities, the metabolic results indicate a faster recovery after high intensity efforts for all athletes, as well as a higher reliance on the fat metabolism for athletes who trained in the running group.